Chemical from wood / Norain Nordin - Nordin, Norain (2011)
This project is a study about chemical from wood. The wood contains cellulose, lignin, extractives and hemi cellulose. This component in wood is valuable in the market after producing a new product or undergoing a new method or process to remove the component from the wood. Meanwhile, the processes should protect the environment soundly. It focuses on structure of wood, chemical composition and component in wood, the commercial product from wood and its processes (method) and the advantages and disadvantages of wood chemistry in general.